2017
DOI: 10.1039/c6ra26340b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene oxide on the geopolymerization mechanism determined by quenching the reaction at intermediate states

Abstract: Schematic diagram of graphene oxide on the geopolymerization of rGO/KGP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Besides, absorption near 3440 cm −1 is assigned to OH vibration of free water. The FT‐IR spectra of the products of CNTs/KGP foams polymerization reaction after adding nanotubes are consistent with the results of various KGP matrix 41 . It is noted that the peak at 1389 cm −1 is attributed to C‐OH stretching bond from CNTs, which remains after geopolymerization process 42 .…”
Section: Resultssupporting
confidence: 85%
“…Besides, absorption near 3440 cm −1 is assigned to OH vibration of free water. The FT‐IR spectra of the products of CNTs/KGP foams polymerization reaction after adding nanotubes are consistent with the results of various KGP matrix 41 . It is noted that the peak at 1389 cm −1 is attributed to C‐OH stretching bond from CNTs, which remains after geopolymerization process 42 .…”
Section: Resultssupporting
confidence: 85%
“…Rietveld quantification of amorphous phases was done by considering the broad humps in powder X-ray diffraction (XRD) spectra, a method that has been applied in literature before [45,46]. Characteristic humps indicating amorphous phases for metakaolin are with 2θ between 18° and 38° [47], respectively between 20° and 30° for fly ash [48].…”
Section: Methodsmentioning
confidence: 99%
“…To measure the mass loss of hardened geopolymer powder samples up to 1000 °C, TGA-DSC (thermogravimetric analysis-differential scanning calorimeter) was performed with a STA 449 F5 Jupiter (Netzsch, Selb, Germany). Therefore, geopolymers were crushed and grinded with acetone which led to rapid evaporation of the water in the sample and to a stop of reaction, a method comparable to storing test specimens in acetone [46] or ethanol/acetone mixtures [47] to stop the reaction. For each measurement 35–40 grams of dry powder was heated up to 1000 °C at a heating rate of 20 °C/min.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of the performance of GO geopolymers at different times, it was found that within 0 to 24 hours, RGO binds well to the geopolymer matrix. As the reaction time increases, the degree of densi-fication increases and the amorphousness of the material [110] decreases [104]. In another study [105] reported the effect of reduced GO content on graphene-geopolymer nanocom-posites.…”
Section: Research Progress Of Graphene Modified Geopolymermentioning
confidence: 98%
“…The results showed that the compressive strength and flexural strength of geopolymers increased by 1.44 times and 2.16 times, respectively, after adding 1% GNPs. Yan et al have conducted a number of graphene-related experi-mental studies [104][105][106]. In the study of the performance of GO geopolymers at different times, it was found that within 0 to 24 hours, RGO binds well to the geopolymer matrix.…”
Section: Research Progress Of Graphene Modified Geopolymermentioning
confidence: 99%